Patterns of lexical correlation and divergence in Casamance. (September 2018) - Watson, Rachel
Abstract: The Casamance region of southern Senegal is characterized by extensive societal and individual multilingualism with many minority languages maintained. Complex patterns of correlation and divergence in the lexica of languages in Casamance reflect the social and historical interactions between populations. This paper examines the lexica of three languages – Joola Kujireray, Joola Banjal and Baïnounk Gubëeher – which stand in differing historical and contemporary relations to one other. It uses a list of over 500 items (for each language) and examines the various constellations of correlation and variance. Attention is paid to the semantic domains represented by these correlations and divergences, and the nature of the correlations, whether due to genetic inheritance or contact. This type of comparison can provide information about the specific details of historical relations between the speakers of these languages, as well as contributing to an understanding of the dynamics of multilingual situations of this type. Highlights: Extensive small-scale multilingualism leads to complex outcomes of language contact. Outcomes can reveal detailed history of contact between populations. Comparison of lexica of small languages provides evidence of micro-histories.